(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Childhood obesity has emerged as a critical public health concern worldwide, with schools increasingly recognized as strategic environments for preventive interventions. This meta-analytic review examines the role of physical education (PE) in mitigating obesity risk among school-aged children by synthesizing evidence from 20 national and international studies published between 2015 and 2025. Data were drawn from multiple scholarly databases, including Scopus, PubMed, Web of Science, Google Scholar, DOAJ, Sinta, and Garuda. A structured search strategy and PRISMA-guided selection process yielded 20 eligible studies, 12 of which provided sufficient data for effect size calculations. The findings reveal that PE contributes significantly to improving key health outcomes, including reductions in body mass index (BMI) and body fat percentage, moderate-to-vigorous physical activity (MVPA) gains, and notable improvements in cardiorespiratory fitness. Behavioral and psychological indicators—such as motivation, self-efficacy, and physical literacy—also improved, suggesting that PE influences both physiological and behavioral pathways associated with obesity risk. While effect sizes ranged from small to moderate, the consistency of positive outcomes across diverse intervention types highlights PE’s essential role in school-based health promotion. The review emphasizes that PE is most effective when implemented frequently, delivered by trained educators, and supported by engaging, student-centred pedagogies such as game-based learning and fitness-oriented instruction. These findings underscore the importance of prioritizing quality PE in educational policies and practices as a scalable, accessible, and sustainable strategy to combat childhood obesity and promote lifelong healthy behaviors.